Upper bound stability analysis of tiered geosynthetic-reinforced soil wall - Chengzhi Xiao; Xiangsheng Meng; Shan Gao; Luqiang Ding (Journal of Rock Mechanics and Geotechnical Engineering)
The tiered geosynthetic-reinforced soil (GRS) walls have been increasingly applied in the high and steep retaining soil structures. However, very little is known about the design method for the tiered GRS wall in practice. This study is aimed at proposing an upper-bound stability analysis method of a tiered GRS wall. The proposed method was firstly validated by the existing results from the centrifuge test and the numerical method, and then a parametric study was performed to investigate the effects of the cohesionless backfill friction angle φ1 and the wall geometric parameters including the offset distance, the total wall height, the batter angle δ, the number of tiers n, and wall height ratio of adjacent tiers on the dimensionless equivalent earth pressure coefficient KT. The analysis results demonstrated that as the φ1 increases, the shear strength of backfill is enhanced and thus the KT or the total reinforcement tensile force decreases, and the KT decreases with the increase of the offset distance at the initial stage and then becomes stable when it reaches a certain critical value. For a fixed offset distance, the KT or the total reinforcement tensile force decreases with the increase of the δ. For the two-tiered GRS walls having the offset distance less than the critical value, the wall with the smaller wall height ratio has a larger KT. Further, the variation of the location of the critical failure surfaces of tiered GRS walls was presented in this study with the variation of the φ1 and the wall geometry.